ANALISIS KONSENTRASI PARTIKEL MIKRO AMBIENT PADA FUNGSI PARU POPULASI URBAN JAKARTA - Reza Aditya Digambiro; Edy Parwanto; Florinda Ilona; Julian Chendrasari; Indah Widya Lestari; Dyah Ayu Woro Setianingrum (Fakultas Kedokteran Universitas Trisakti, 2024)
Introduction: The potential impact on lung function due to high exposure to ambient microparticles in cities such as Jakarta has not been comprehensively studied. The background of this research is based on the lack of studies regarding the impact of high micro-particle exposure in major cities like Jakarta on lung function. Research Objective: The purpose of this study is to investigate the relationship between the dominant levels of ambient micro-particle concentration in urban areas of Jakarta and changes in spirometry indices among its residents. Method: A cross-sectional approach was used to determine the relationship between ambient micro-particle concentration and irregularities in spirometry indices among the urban population of Jakarta. This study involved 187 adults, aged between 20 to 65 years, mostly from the busy urban sectors of Jakarta. Statistical techniques of association and logistic regression were used for the assessment of the collected data. Results: The average exposure to ambient micro-particles was 315 µg/m³. Aberrations in spirometry indices were detected in 41.2% of participants. A significant relationship was found between high micro-particle concentrations and anomalies in spirometry readings among urban residents of Jakarta. This correlation remained significant after considering confounding factors such as gender, duration of exposure, local ventilation quality, smoking habits, and prevailing humidity. Conclusion: The results of this analysis suggest that the dominant levels of ambient micro-particles in the urban areas of Jakarta may play an important role in causing variations in spirometry results among its inhabitants..